2015
DOI: 10.1002/acr.22543
|View full text |Cite
|
Sign up to set email alerts
|

Expert Panel Consensus on Assessment Checklists for a Rheumatology Objective Structured Clinical Examination

Abstract: This single-round expert panel survey established consensus on 133 items to assess on 11 proposed ROSCE stations. The method used in this study, which can engage a diverse geographic representation and employs rigorous statistical methods to establish checklist content agreement, can be used in any medical field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Our study has a number of important strengths: we recruited a large expert sample relative to other comparable studies in arthritis care,12 13 20 27 30 31 our sample was cross-disciplinary with a spread of practice locations across the country, our response rate remained very high across all three rounds, and we achieved a high level of support for the final set of themes. Our sample was purposely weighted towards rheumatologists to reflect the discipline most usually involved across the continuum of care from contraception through to early parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has a number of important strengths: we recruited a large expert sample relative to other comparable studies in arthritis care,12 13 20 27 30 31 our sample was cross-disciplinary with a spread of practice locations across the country, our response rate remained very high across all three rounds, and we achieved a high level of support for the final set of themes. Our sample was purposely weighted towards rheumatologists to reflect the discipline most usually involved across the continuum of care from contraception through to early parenting.…”
Section: Discussionmentioning
confidence: 99%
“…In the nursing area, few specialties apply this evaluation format -one of them is the Brazilian Association of Nursing in Intensive Care, which uses the simulation of procedures and discuss clinical cases (33) . Some medical specialties apply the analysis of clinical exams, discussion of cases, and use simulated practical stations or Structured Objective Clinical Examination (OSCE) to evaluate specialists' expected competencies in intensive care, orthopedics, and rheumatology (34)(35)(36) . In this study, the literature recommendation regarding the OSCE was followed, which allows evaluating clinical skills (37) and mainly the application of knowledge in practice (38) .…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Using a standard checklist is one of the criteria for the quality of the objective structured clinical examination. [ 7 ] Mansourian et al . (2017) reported that the content validity of the checklist for evaluating dental students was 0.8 and its reliability coefficient was 0.9.…”
Section: Discussionmentioning
confidence: 99%